DAMPAK GANGGUAN (ERROR) SISTEM CORETAX TERHADAP KUALITAS PELAYANAN SPT TAHUNAN WAJIB PAJAK - Yulfa Widiastuti; Syahidatul Khoiriyah; Wilda Waladatus Sholehah; Linda Setyowati; Zainul Latif Al-Hadad; Kartika Marella Vanni (LPPM Universitas Negeri Jakarta, 2025)
This research aims to analyze the impact of technical disruptions (errors) in the Coretax system implemented by the Directorate General of Taxes since January 1, 2025, on the quality of taxpayer services during the Annual Tax Return (SPT) reporting period. The implementation of Coretax is part of the national digital tax reform based on Presidential Regulation No. 40 of 2018 and its technical foundation in Minister of Finance Regulation No. 81 of 2024. However, since its launch, the system has encountered various technical issues that hinder taxpayers in fulfilling their obligations. This study uses a descriptive qualitative approach through a literature review, analyzing data from official DGT reports, credible media, and academic studies from 2020–2025. The results show that disruptions such as Error 502, login failures, OTP issues, NIK-NPWP data mismatches, and server overloads affect service quality, including reliability, responsiveness, accessibility, information accuracy, taxpayer satisfaction, and compliance. DGT responded through parallel systems, penalty-free policies, and gradual improvements.